Hubungan sikap peduli lingkungan dengan partisipasi dalam memelihara lingkungan pada pedagang di Pasar Kalibaru Cilincing, Jakarta Utara - Titania Puspita Anggraeni; M Japar; I Syafrudin (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2021)
Participation in maintaining the environment can be influenced by the attitude, because it has will elicit a response to act. The purpose of this study was to obtain empirical data regarding the relationship between environmental care attitudes and participation in preserving the environment for traders at Kali Baru Cilincing Market, North Jakarta. The method used was a simple regression method with a quantitative approach. This research was conducted on 72 traders. The results show that simple linear regression Ŷ=0,439+0,787X. Regression significance test obtained Fcount 39,964 > Ftable 3,98, this indicates the regression model was significant. In the linearity test, Fcount 0,638 < Ftable 1,775, thus the regression was linear. Furthermore, the product moment correlation test obtained rcount 0,576 > rtable 0,231, so there was a positive relationship. The significance test of the relationship was obtained tcount 7,201 > ttable 1,994, meaning that the relationship between Environmental Care Attitude (X) and Participation in Preserving the Environment (Y) was significant. The correlation coefficient of 0,576. The coefficient of determination of 0,331 means that the X variable contributes to the Y variable by 33,1%. Based on this research, there was a positive relationship between environmental care attitudes and participation in preserving the environment.